Assessment of Dentists’ Existing Knowledge towards Triclosan and Its Impact on General Health - Raskar , Manali J.; Mathur , Anmol; Desai , Ruttika; Rana , Avni; Mathur , Aditi (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Background: Triclosan is widely used in hygiene products. Recently, FDA has banned over-the-counter products containing triclosan due to its potentially harmful effects on health. Aim: This study aimed to find dentists’ knowledge regarding the ill effects of triclosan on general health, the status of any ban being imposed on triclosan around the world, and their knowledge of any alternatives available. Methods: This cross-sectional study made use of a self-designed questionnaire to collect data. Two experts did face validity of the questionnaire, and six experts from Pharmaceutical Science did content validity. A total of 195 dentists' were administered the questionnaire utilizing a Google form. Results: All participants filled out the questionnaire, of which 149 (76%) were males and 46 (23.5%) were females. 45% of dentists had experienced between 5-9 years and 39.4% had more than 10 years of experience. Eta correlation showed that the experience of the dentist had a 42% influence on their knowledge scores. Point-biserial correlation indicated that female dentists showed poor knowledge scores when compared to males. Conclusion: The present study found that although dentists knew about triclosan, their knowledge regarding its safety was limited. There was mixed opinion regarding banning triclosan in the country. Considering the limited literature on the subject, this study serves as the first step to assess the awareness of the dental community towards triclosan.